204 Changes in Physical Activity During the COVID-19 Pandemic Associated with Changes in Sleep. (3rd May 2021) - Abdi, Harun; Killgore, William; Wills, Chloe; Kennedy, Kathryn; Charest, Jonathan; Knowlden, Adam; Grandner, Michael
Abstract: Introduction: The COVID-19 global pandemic has likely led to changes in physical activity as behavioral patterns were disrupted. This is important because sleep and physical activity are interrelated and promote health, and well-being. This study examined whether changes to physical activity were related to changes to sleep health as a result of the COVID-19 pandemic. Methods: A sample of N=419 US adults completed online surveys about sleep and COVID-19 experiences. Participants were asked to estimate the number of minutes per day they engaged in physical activity during the pandemic, as well as before. These were subtracted from each other, and a difference score was computed. Then, responses were categorized as no change (<=15 mins difference), 16-45 minutes more or less activity, or 46+ minutes more or less activity (5 categories total). Outcome variables included the degree to which participants believed that due to the pandemic, they experienced (1) more schedule regularity, (2) better sleep, (3) worse sleep, (4) more difficulty falling asleep, (5) more difficulty maintaining sleep, (6) more sleepiness, and (7) more napping. Ordinal regressions were adjusted for age, and sex. Results: Those who increased their activity by over 45 minutes per day reported that they were less likely to experience more daytime sleepiness (oOR=0.28, p<0.02). Those who decreased their activity by over 45 minutes per day reported that they were more likely to experience worse sleep (oOR=2.38, p<0.01) and less likely to experience a more regular schedule (oOR=0.37, p<0.003) than prior to the pandemic. Conclusion: Overall, those who increased their physical activity since the beginning of the pandemic reported less daytime sleepiness; and those who decreased their physical activity reported worse sleep experiences and a more irregular schedule. The relationship between physical activity and sleep during the pandemic may be bidirectional. Support (if any): R01MD011600, R01DA051321